The Inhibition of Bromodomain and Extraterminal Domain (BET) Proteins Protects Against Microglia-Mediated Neuronal Loss In Vitro - Marta Matuszewska; Anna Wilkaniec; Magdalena Cieślik; Marcin Strawski; Grzegorz A. Czapski (Biomolecules)
Neuroinflammation is a key feature of all neurodegenerative disorders, including Alzheimer’s disease, and is tightly regulated by epigenetic mechanisms. Among them, bromodomain and extraterminal domain (BET) proteins play a crucial role by recognizing acetylated histones and acting as transcriptional co-regulators to modulate gene expression. This study investigates the potential of inhibiting BET proteins in preventing microglia-mediated neuronal damage in vitro. Murine BV2 microglial cells were exposed to lipopolysaccharide (LPS) or amyloid-β (Aβ) to induce an inflammatory response, and the subsequent effects on murine HT22 neuronal cells were examined. Among the BET proteins tested, only Brd4 was significantly upregulated in BV2 cells upon pro-inflammatory stimulation. JQ1, a potent pan-inhibitor of BET proteins, suppressed LPS-induced upregulation of pro-inflammatory cytokine mRNA levels, including Il1b, Il6, and Tnf, in BV2 microglia. Pre-treatment with JQ1 attenuated the cytotoxicity of LPS-activated BV2 cells toward neurons. Additionally, conditioned media from Aβ fibril-stimulated BV2 cells induced neuronal cell death, which was partially prevented by pre-treatment with JQ1. Co-culture assays further demonstrated the beneficial effect of BET inhibition. Our findings suggest that targeting BET proteins may offer a neuroprotective strategy by modulating microglial activation, potentially providing therapeutic benefits in neurodegenerative diseases.